Binary homodyne detection for observing quadrature squeezing in satellite links - Müller, Christian; Seshadreesan, Kaushik P.; Peuntinger, Christian; Marquardt, Christoph (Physical Review Research, 2020)
Optical satellite links open up new prospects for realizing quantum physical experiments over unprecedented length scales. We analyze and affirm the feasibility of detecting quantum squeezing in an optical mode with homodyne detection of only one bit resolution, as is found in satellites already in orbit. We show experimentally that, in combination with a coherent displacement, a binary homodyne detector can still detect quantum squeezing efficiently even under high loss. The sample overhead in comparison to nondiscretized homodyne detection is merely a factor of 3.3.
CRIS-Team WoS Importer:2021-01-22

Distillation of squeezing using an engineered pulsed parametric down-conversion source - Dirmeier, Thomas; Tiedau, Johannes; Khan, Imran; Ansari, Vahid; Müller, Christian; Silberhorn, Christine; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2020)
Hybrid quantum information processing combines the advantages of discrete and continues variable protocols by realizing protocols consisting of photon counting and homodyne measurements. However, the mode structure of pulsed sources and the properties of the detection schemes often require the use of optical filters in order to combine both detection methods in a common experiment. This limits the efficiency and the overall achievable squeezing of the experiment. In our work, we use photon subtraction to implement the distillation of pulsed squeezed states originating from a genuinely spatially and temporally single-mode parametric down-conversion source in non-linear waveguides. Due to the distillation, we witness an improvement of 0.17 dB from an initial squeezing value of -1.648 +/- 0.002 dB, while achieving a purity of 0.58, and confirm the non-Gaussianity of the distilled state via the higher-order cumulants. With this, we demonstrate the source's suitability for scalable hybrid quantum network applications with pulsed quantum light. (C) 2020 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2020-11-13

Noise-powered probabilistic concentration of phase information - Usuga, Mario A.; Müller, Christian; Wittmann, Christoffer; Marek, Petr; Filip, Radim; Marquardt, Christoph; Leuchs, Gerd; Andersen, Ulrik L. (Nature Physics, 2010)
Phase-insensitive optical amplification of an unknown quantum state is known to be a fundamentally noisy operation that inevitably adds noise to the amplified state. However, this fundamental noise penalty in amplification can be circumvented by resorting to a probabilistic scheme as recently proposed and demonstrated in refs 6, 7, 8. These amplifiers are based on highly non-classical resources in a complex interferometer. Here we demonstrate a probabilistic quantum amplifier beating the fundamental quantum limit using a thermal-noise source and a photon-number-subtraction scheme. The experiment shows, surprisingly, that the addition of incoherent noise leads to a noiselessly amplified output state with a phase uncertainty below the uncertainty of the state before amplification. This amplifier might become a valuable quantum tool in future quantum metrological schemes and quantum communication protocols. © 2010 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

Optimally cloned binary coherent states - Müller, Christian; Leuchs, Gerd; Marquardt, Christoph; Andersen, U. L. (Physical Review A, 2017)
Binary coherent state alphabets can be represented in a two-dimensional Hilbert space. We capitalize this formal connection between the otherwise distinct domains of qubits and continuous variable states to map binary phase-shift keyed coherent states onto the Bloch sphere and to derive their quantum-optimal clones. We analyze the Wigner function and the cumulants of the clones, and we conclude that optimal cloning of binary coherent states requires a nonlinearity above second order. We propose several practical and near-optimal cloning schemes and compare their cloning fidelity to the optimal cloner.
CRIS-Team Scopus Importer:2022-06-05

Parsing polarization squeezing into Fock layers - Müller, Christian; Madsen, Lars S.; Klimov, Andrei B.; Sanchez-Soto, Luis L.; Leuchs, Gerd; Marquardt, Christoph; Andersen, Ulrik L. (Physical Review A, 2016)
We investigate polarization squeezing in squeezed coherent states with varying coherent amplitudes. In contrast to the traditional characterization based on the full Stokes parameters, we experimentally determine the Stokes vector of each excitation subspace separately. Only for states with a fixed photon number do the methods coincide; when the photon number is indefinite, we parse the state in Fock layers, finding that substantially higher squeezing can be observed in some of the single layers. By capitalizing on the properties of the Husimi Q function, we map this notion onto the Poincaré space, providing a full account of the measured squeezing.
CRIS-Team Scopus Importer:2022-06-05

Quadrature phase shift keying coherent state discrimination via a hybrid receiver - Müller, Christian; Usuga, M. A.; Wittmann, Christoffer; Takeoka, M.; Marquardt, Christoph; Andersen, U. L.; Leuchs, Gerd (New Journal of Physics, 2012)
We propose and experimentally demonstrate a near-optimal discrimination scheme for the quadrature phase shift keying (QPSK) protocol. We show in theory that the performance of our hybrid scheme is superior to the standard scheme-heterodyne detection-for all signal amplitudes and underpin the predictions with our experimental results. Furthermore, our scheme provides hitherto the best performance in the domain of highly attenuated signals. The discrimination is composed of a quadrature measurement, a conditional displacement and a threshold detector. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05

Quantum-limited measurements of optical signals from a satellite in geostationary earth orbit - Günthner, Kevin; Khan, Imran; Elser, Dominique; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Quantum-limited measurements of signals from geostationary earth orbit - Elser, Dominique; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (European Conference on Optical Communication, ECOC, 2016)
Quantum key distribution (QKD) has been implemented in metropolitan area networks around the world. Optical satellite communication is seen as suitable to provide the missing long-haul interconnections. We validate this approach by quantum measurements of optical signals from space.
CRIS-Team Scopus Importer:2021-06-29

Quantum Limits of Coherent Beam Combining - Leuchs, Gerd; Müller, Christian; Sedlmeir, Florian; Chatterjee, Sourav; Haarlammert, Nicoletta; Jauregui, Cesar; Schreiber, Thomas; Limpert, Jens; Tunnermann, Andreas; Marquardt, Christoph (2018 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2018, 2019)
Coherent beam combining refers to the process of generating a bright output beam by merging independent input beams with locked relative phases. We report the first quantum mechanical noise limit calculations for coherent beam combining and compare our results to quantum-limited amplification. We highlight a favourable noise scaling for both pure and noisy input states.
CRIS-Team Scopus Importer:2019-05-21

Quantum measurements of signals from the Alphasat TDP1 laser communication terminal - Elser, D.; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, K.; Tröndle, D.; Heine, F.; Seel, S.; Greulich, P.; Zech, H.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Quantum optics [1] can be harnessed to implement cryptographic protocols that are verifiably immune against any conceivable attack [2]. Even quantum computers, that will break most current public keys [3, 4], cannot harm quantum encryption. Based on these intriguing quantum features, metropolitan quantum networks have been implemented around the world [5-15]. However, the long-haul link between metropolitan networks is currently missing [16]. Existing fiber infrastructure is not suitable for this purpose since classical telecom repeaters cannot relay quantum states [2]. Therefore, optical satellite-to-ground communication [17-22] lends itself to bridge intercontinental distances for quantum communication [23-40].
CRIS-Team Scopus Importer:2021-06-29

The standard quantum limit of coherent beam combining - Müller, Christian; Sedlmeir, F.; Martynov, V. O.; Marquardt, Christoph; Andrianov, A. V.; Leuchs, Gerd (New Journal of Physics, 2019)
Coherent beam combining refers to the process of generating a bright output beam by merging independent input beams of individually diffusing relative phases by locking them to each other. We report the first quantum mechanical noise limit calculations for coherent beam combining and compare our results to quantum-limited amplification. Our coherent beam combining scheme is based on an optical Fourier transformation which renders the scheme compatible with integrated optics combined with feed-back stabilization of the relative phases. The scheme can belayed out for an arbitrary number of input beams and approaches the shot noise limit for a large number of inputs.
CRIS-Team WoS Importer:2019-10-15